Willingness to pay for treatment with highly active antiretroviral (HAART) drugs: a rural case study in Cameroon - Kenneth Ngwambokong Muko; Valentine Che Ngwa; Leslie Chigang; Igbinosum Gladys Ngwa; Anke Meiburg; Elvis Neba Shu (SAHARA-J, 2004)
This paper reports on the willingness of HIV/AIDS patients to pay for the most affordable triple therapy combination of antiretrovirals in a local setting in Cameroon. Questionnaires were used to evaluate willingness to pay, and patients who could still afford their medication 6 months after the survey were also investigated, to give an indication of actual ability to pay. In addition, oral interviews were carried out for clarification. In all, 84 patients out of a total of 186 were involved in the study. Results indicated that more men (39%) were willing to pay than women (22%), although more women (56%) were afflicted than men. Willingness to pay was directly dependent on cost with 69%, 22% and 9% of respondents indicating willingness to pay $1, $2 and $3 a day respectively. After 6 months of treatment, 22% of patients were still on therapy. A majority of patients stopped taking the drugs after 6 months due to financial constraints. Apart from cost, stigma, disbelief and side-effects of medication were found to be the main factors militating against willingness to pay. Improved counselling and provision of information, reduced cost of drugs including laboratory tests, and destigmatisation programmes are recommended to improve patients' ability to pay for antiretrovirals.